Breaking Barriers: The Power of Psychological Hardiness and Effective Rumination in Countering Social Undermining’s Impact on Employee Engagement - Henna Gul Nisar; Saniha Nawaz; Farwida Javed; Muhammad Shahzad Sadiq; Deyi Xu (International Journal of Business and Economic Affairs, 2025)
The main aim of this study is to find the effect of social undermining on employee work engagement. Moreover, this study also finds the moderating role of psychological hardiness on the relationship between social undermining and effective rumination. Furthermore, this research also investigates the mediating role of employee effective rumination between social undermining and employee work engagement. A total of (n=300) sample was selected for this study by using convenience sampling technique. SPSS and AMOS were used for the hypothesized relationship between main variables of the study. By applying two important theories of organizational behavior i.e. Self-regulation theory and fairness theory. The results of this study show that social undermining has negative and significant effect of employee work engagement. Social undermining has also a negative and significant effect on effective rumination. The results also show that psychological hardiness significantly moderates the relationship between social undermining and effective rumination. Furthermore, results also revealed that effective rumination significantly mediates the relationship between social undermining and employee work engagement. Further this study will open new avenues for practitioners and scholars.